DAMPAK PENYAJIAN KEMBALI EPS DAN CFPS TERHADAP RETURN SAHAM - Sinaga, Imelda (Jurnal Riset Akuntansi dan Keuangan, 2014)
The problem in this study is whether there is a positive influence of CFPS and EPS before and after restatement in giving positive impact on stock returns. The sample used in EPS before and after the restatement, while as many as 102 samples meanwhile CFPS before and after restatement using 82 sample companies listed on the Stock Exchange. Independent variables used in this study are the earnings per share and cash flow per share and the dependent variables used in this study is the stock return. Test equipment used in this study using multiple regression statistical model          The results of this study demonstrate that EPS before restatement did not impact significantly on the stock returns which indicates that investors have been aware that there is signal to improve the EPS before the restatement. EPS after restatement had no significant effect on return, this indicates that the new information is in accordance with the Market Efficiency hypothesis is that will make the market participants to react and take action to respond that new information. CFPS before and after restatement also had no significant effect on stock returns because investors do not use operating cash flow information as a basic for investment decisions. This can have implications on investors who use financial statements to make right decisions on the location of their assets in the companies that perform restatement as well for the company itself that financial report restatement can be made if it is seen as a form of commitment and sense of responsibility to the market to provide trustable information